Intramyometrial pregnancy after cryopreserved embryo transfer: a case report - Yuan Liu; Yu Wu (BMC, 2020)
Abstract Background Intramyometrial pregnancy is a rare subtype of ectopic pregnancy. The cases following IVF-ET were few reported in recent years. The etiological factors include previous uterine trauma like myomectomy, salpingectomy, dilatation and curettage, assisted reproductive technologies and adenomyosis. Early diagnosis is difficult to make due to its various manifestation. The medical treatment includes conservative management with surgical excision, aortic balloon occlusion, uterine artery embolization, MTX etc. Sometimes hysterectomy was performed due to delayed diagnosis. Case presentation In this article, we presented a case of a 28 years old woman who had cryopreserved embryo transfer with a history of right side salpingectomy. We suspected it a right adnexa ectopic pregnancy at the first place, especially the right fallopian interstitial or right uterus cornu due to ultrasonography and medical history. The product of conception was discovered embedded in the myometrium and protruding out from the right side of the posterior uterine wall, with seemingly no connection with uterine cavity nor fallopian tubes. The diagnosis of intramural pregnancy was made intraoperatively and validated after pathological report. The interventions were made early enough that exploratory laparoscopy, hysteroscopy and conservative surgical excision were successfully performed at 7 weeks' gestation preserving the fertility. Conclusions It is important for clinicians to be aware of risk factors of intramural pregnancy and maintain an index of suspicion in ART treatment. Ultrasound and laparoscopy are essential managements for early diagnose which make conservative treatment possible and prevent life-threatening consequences.